2022
DOI: 10.1021/acs.cgd.2c00005
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II) Complexes of 4-(Alkyldisulfanyl)-2,6-di(pyrazolyl)pyridine Derivatives. Correlation of Spin-Crossover Cooperativity with Molecular Structure Following Single-Crystal-to-Single-Crystal Desolvation

Abstract: The complex salts [Fe( L 1 ) 2 ]X 2 ( 1X 2 ; L 1 = 4-(isopropyldisulfanyl)-2,6-bis(pyrazolyl)pyridine; X – = BF 4 – , ClO 4 – ) form solvated crystals from common organic solvents. Crystals of 1X 2 ·Me 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 120 publications
(189 reference statements)
1
13
0
Order By: Relevance
“…The large ΔΘ distortion in 1­[ClO 4 ] 2 is a property of its inner coordination sphere, which should not influence its thermal hysteresis unless it reflects a larger structure change in the molecule as a whole . Hysteretic spin-transitions in [Fe­(bpp R,Y ) 2 ]­X 2 derivatives can be associated with a rearrangement of the ligands about the metal ion during SCO, which manifests in their trans -N­{pyridyl}–Fe–N­{pyridyl} angle (ϕ; Tables and ). , However, the change in ϕ between the spin states of 1­[ClO 4 ] 2 , Δϕ = −0.55(9)°, is too small to be significant (Table S7). Rather, the SCO hysteresis shown by 1­[BF 4 ] 2 and 1­[ClO 4 ] 2 may reflect the steric influence of their fluoro substituents on their crystal packing, which leads to a significant conformational distortion of one L ligand (Figures S8–S9).…”
Section: Discussionmentioning
confidence: 99%
“…The large ΔΘ distortion in 1­[ClO 4 ] 2 is a property of its inner coordination sphere, which should not influence its thermal hysteresis unless it reflects a larger structure change in the molecule as a whole . Hysteretic spin-transitions in [Fe­(bpp R,Y ) 2 ]­X 2 derivatives can be associated with a rearrangement of the ligands about the metal ion during SCO, which manifests in their trans -N­{pyridyl}–Fe–N­{pyridyl} angle (ϕ; Tables and ). , However, the change in ϕ between the spin states of 1­[ClO 4 ] 2 , Δϕ = −0.55(9)°, is too small to be significant (Table S7). Rather, the SCO hysteresis shown by 1­[BF 4 ] 2 and 1­[ClO 4 ] 2 may reflect the steric influence of their fluoro substituents on their crystal packing, which leads to a significant conformational distortion of one L ligand (Figures S8–S9).…”
Section: Discussionmentioning
confidence: 99%
“…Spiral architectures of iron(II) are an interesting area to investigate due to the fascinating structure and cooperative SCO behavior, as metal centers in those will lead up to three different spin states: LS-LS, LS-HS and HS-HS [ 54 , 55 , 56 ]. These spin states can be related to cooperativity.…”
Section: Magnetic Properties Of Iron(ii) Spin-crossover Schiff Base S...mentioning
confidence: 99%
“…Spiral iron(II) SCO architectures are interesting due to the fact that they have three-dimensional structures. As positive cooperativity occurs between metal centers, the SCO behaviors have been found in different forms compared as mononuclear analogues [ 32 , 54 , 55 , 56 ]. Positive cooperativity can lead to one-step spin switching of both metal centers (i.e., [HS-HS] to [LS-LS] or vice versa) in which a sharp, abrupt and/or hysteretic loop SCO can be attained ( Figure 2 b,c) [ 57 , 58 , 59 , 60 ].…”
Section: Magnetic Properties Of Iron(ii) Spin-crossover Schiff Base S...mentioning
confidence: 99%
“…The cycling is also accompanied by a steady rise of χT value in the 5 K-to-275 K region, as recently observed for an iron(II)-BPP system by Halcrow and co-workers. 26 A fraction of the complex molecules in the mixed phase, obtained after the 11 th cycle, undergoes gradual SCO, as depicted in Figure 4. To further confirm the occurrence of temperature-induced spin-state switching in 1•CH3CN, differential scanning calorimetric (DSC) studies were performed, as shown in Figure 5a.…”
Section: •Ch3cnmentioning
confidence: 99%